(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The aim of this work has been the investigation of structure/activity dependence of new porphyrines to improve their radiosensitizing effects. In this work it was shown that the cytotoxicity of water-soluble porphyrines depends on the type of central metal atom and ranges in the following order: ZnTOEt4PyP>MnTOEt4PyP>AgTOEt4PyP>FeTOEt4PyP>H2TOEt4PyP>CoTOEt4PyP>CuTOEt4PyP. Only AgTOEt4PyP and CuTOEt4PyP porphyrines demonstrated the radiosensitizing activity (DMF=1.9). Thus, the radiosensitizing activity of porphyrines depends on the structure, and structure modifications can be a way to improve their anticancer activity and pharmacological features.